2012
DOI: 10.1210/en.2012-1301
|View full text |Cite
|
Sign up to set email alerts
|

GPRC6A Mediates the Effects of l-Arginine on Insulin Secretion in Mouse Pancreatic Islets

Abstract: L-arginine (l-Arg) is an insulin secretagogue, but the molecular mechanism whereby it stimulates insulin secretion from β-cells is not known. The possibility that l-Arg regulates insulin secretion through a G protein-coupled receptor (GPCR)-mediated mechanism is suggested by the high expression of the nutrient receptor GPCR family C group 6 member A (GPRC6A) in the pancreas and TC-6 β-cells and the finding that Gprc6a(-/]minus]) mice have abnormalities in glucose homeostasis. To test the direct role of GPRC6A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 42 publications
4
61
0
Order By: Relevance
“…Although the H1 haplotype, without the deleterious STOP-SNP, is quite rare in the Danish population, we do observe a statistically significant increased first phase insulin response among male carriers. This aligns with the observations that exon 2 GPRC6A knockout mice display lower levels of insulin release than wild type male mice (which have the H3 haplotype) (13,25). However, the low number of H1 haplotype carriers in the Danish cohort warrants confirmation in larger (African) cohorts before drawing conclusions about the biological significance of the observation.…”
Section: Discussionsupporting
confidence: 83%
“…Although the H1 haplotype, without the deleterious STOP-SNP, is quite rare in the Danish population, we do observe a statistically significant increased first phase insulin response among male carriers. This aligns with the observations that exon 2 GPRC6A knockout mice display lower levels of insulin release than wild type male mice (which have the H3 haplotype) (13,25). However, the low number of H1 haplotype carriers in the Danish cohort warrants confirmation in larger (African) cohorts before drawing conclusions about the biological significance of the observation.…”
Section: Discussionsupporting
confidence: 83%
“…␤-cell-specific G␣ i2 -deficient mice showing significantly decreased plasma insulin levels following glucose challenge are consistent with those from global and ␤-cell-deficient GPRC6A mice (25). Future studies will have to clarify whether the concordant findings in the GPRC6A-deficient and G␣ i2 -deficient mice are mechanistically connected.…”
Section: Discussionsupporting
confidence: 60%
“…Two recent studies describe mouse models lacking the nutrient receptor GPCR family C group 6 member A (GPRC6A), which is a receptor for L-amino acids (35), in particular those with basic side chains (24,36). Whereas Smajilovic et al (31) found evidence for the expression of GPRC6A in pancreatic islets but found no evidence that the L-arginine-induced insulin secretion was affected by GPRC6A deletion, Pi et al (25,26) reported that GPRC6A mediates osteocalcin-and L-arginine-induced insulin secretion from ␤-cells in global and ␤-cell-specific GPRC6A-deficient mouse models. Our data from global and ␤cko mice over time.…”
Section: Discussionmentioning
confidence: 99%
“…GPRC6A and Calcium, Amino Acids, and Osteocalcin. GPRC6A has been reported to sense both nutrientderived factors, such as calcium and amino acids (Christiansen et al, 2007;Pi et al, 2012); testosterone (Pi et al, 2010); and the bone-derived hormone osteocalcin (Oury et al, 2011;Pi et al, 2011 Although ligands for orphan GPCRs continue to be identified, there is also evidence that some may have functions in the absence of an endogenous transmitter through constitutive activity or by modulating the activity of other GPCRs via dimerization. These receptors may still represent a druggable target by the discovery of synthetic ("surrogate") ligands.…”
Section: B Class Bmentioning
confidence: 99%